الحماية المدنية لقواعد حوكمة الشركات التجارية المتعلقة بمحافظي الحسابات - معمر, خالد; شارف, بن يحي (مجلة البحوث في الحقوق والعلوم السياسية, 2022)
يتضمن هذا البحث الحديث عن موضوع مهم جدا في مسألة حوكمة الشركات التجارية وهو إظهار مواطن التأثير من قبل محافظ الحسابات و إبراز مبادئ الحوكمة وتحقيقها في الشركة التجارية وما يتبعها من وعي لدى أصحاب المصالح وما ينتج عنه من زيادة الثقة في تعاملات الشركة وربحيتها ،لذلك تم الاهتمام بفحص النصوص المنظمة لتعيين محافظي الحسابات وبيان مهامهم ومسؤولياتهم وتقدير كفاية الحماية المدنية التي تحتوي عليها هذه النصوص ومدى ملاءمتها وخدمتها لقواعد الحوكمة. ومن ناحية أخرى حوكمة المسؤولية في حد ذاتها من خلال توقيعها على محافظي الحسابات الذين يستحقون حقا المساءلة وإعفاء من قاموا بواجباتهم التي فرضها القانون على أتم وجه من خلال تكريس القواعد التي تعفي من المسؤولية والأخرى التي تأمنهم منها. This research includes talking about a very important topic in the issue of business governance, which is to show the influence of the portfolios of accounts and to highlight the principles of governance and its realization in the commercial company and the subsequent awareness of stakeholders and the resulting increased confidence in the company's dealings and profitability, so attention was paid to examining the texts governing the appointment of account governors and showing their functions and responsibilities and assessing the adequacy of civil protection contained in these texts and their suitability and service to governance rules. On the other hand, governance of responsibility per se by signing it to the auditors who truly deserve accountability and exempting those who have fully carried out their duties imposed by law by enshrining the rules that exempt them from liability and those from which they are safe.
Keywords: Comptable; Développement; Gouvernance d'entreprise; Responsabilité civile; التنمية; حوكمة الشركات; محافظ الحسابات; مسؤولية مدنية